2010
DOI: 10.1504/ijmc.2010.030518
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising fun in mobile commerce environments

Abstract: Consumers use mobile commerce services to hedonically experience 'fun'. This research explores what consumer-oriented service strategies have been adopted to enhance the fun experience. This research is a case study using grounded theory to develop the conceptual model, represented by 15 propositions, suggesting that attention be focused in three areas; content, social and self orientations. The first, relates to the way in which the service is constructed or the service content orientation. Secondly, the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Therefore, identifying novel methodologies for analysing mobile consumer behavioural habits on smartphones and predicting future behaviour patterns based on consumer data are required. An overview of previous studies showed that research in the area of mobile marketing has been explored from the perspective of businesses, rather than that of consumers (Büyüközkan, 2009;Davis & Chaudhri, 2012;Huang, 2011;Huang, 2012;Pantano, 2016;Scharl et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, identifying novel methodologies for analysing mobile consumer behavioural habits on smartphones and predicting future behaviour patterns based on consumer data are required. An overview of previous studies showed that research in the area of mobile marketing has been explored from the perspective of businesses, rather than that of consumers (Büyüközkan, 2009;Davis & Chaudhri, 2012;Huang, 2011;Huang, 2012;Pantano, 2016;Scharl et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, Figures 2a and 2b and Table 2 suggest that since 2001 there has been a significant increase in both the number of nodes (distinct key words and pat- (21), system (20), mobile (20), device (20), messag (15), network (15), communicat (14), commerc (14), transact (14), location (12), user (11), service (11), wireless (11), instant (10), real-time (10), information (10), profil (9), SMS (8), advertis (5), consumer (5) (15), compet (12) circles imply more patent applications and more squares imply more diverse patents, at least as far as semantics and topical areas are concerned. However, the average degree of patent application titles, which serves as an indication of the number of nondescriptive words in patent titles, has ranged, on average, between 7 and 8 words for all the considered years.…”
Section: Evolution Of M-commerce Innovationsmentioning
confidence: 95%
“…Kumar and Benbasat noted that "shoppers have become guests, shopping has become an experience and malls have become entertainment centers with communities" [36, p. 8], and recent studies have drawn on social presence theory [67] to explain how important it is for an Internet medium to allow human contact and sociability [16,80]. "Social shopping," that is, mobile commerce with integrated social networking aspects, has been categorized in prior literature as a hedonic activity [2,15,23], with authors arguing that the sense of community with friends and total strangers offered by "social shopping" generates a playful experience. It has been noted, in particular, that consumers' use of m-commerce systems is frequently enhanced with such "playful, interesting, challenging, and meaningful" activities [19, p. 79].…”
Section: Related Literaturementioning
confidence: 99%
“…Consumers concentrate more on the capability of media information dissemination than the sender's emotional state (Pollach, 2008), and richer media can result in a more positive affective state when feelings and emotions are able to be shared during the information exchange process (Pollach, 2008;Daft and Lengel, 1986;Daft et al, 1987;Lengel and Daft, 1989). Consumers using new media-rich mobile technologies can therefore enrich their mobile experience as well as improving pleasure and arousal during usage (Li et al, 2012;Davis, 2010). This leads to the following hypotheses: …”
Section: Media Richnessmentioning
confidence: 99%